Salud y riesgos ocupacionales por el manejo de plaguicidas en campesinos agricultores, municipio de Marinilla, Antioquia, 2009 (2011)
ABSTRACT: The agricultural sector has played a key role in the development of Colombia’s economy and rural communities. The Marinilla municipality, located in the eastern area of the department of Antioquia, bases its economy in agriculture and livestock activities. This requires the use of a wide variety of chemical products that pose health risks. Objective: to describe the occupational and health risks of the farmers who use pesticides in Marinilla. Methodology: a descriptive study with multistage sampling and a sample of 157 farmers. Results: 64.9% of the farmers combine more than two chemicals. 83% of them have received no training on safe handling of agricultural chemical products. Approximately 80% of these individuals do not use the appropriate protective equipment to perform this task. Only 2.5 % of the farmers have occupational risks insurance. The most common disease was acute respiratory infection (78%). 22.3% have suffered from acute intoxication, and 14% (11) of the female farmers who have ever been intoxicated had abortions, premature births, or bore children with some kind of disability. A statistically significant difference was found between the age of farmers and pesticide usage time. No statistical difference was found between low schooling level and knowledge of the risks posed by chemical products. Conclusion: most agricultural workers have not been trained in safety standards; therefore, they disregard all kinds of safety measures during their work, and act without safety in mind and without personal hygiene habits.